2019
DOI: 10.1128/jvi.02013-18
|View full text |Cite
|
Sign up to set email alerts
|

Residues on Adeno-associated Virus Capsid Lumen Dictate Interactions and Compatibility with the Assembly-Activating Protein

Abstract: The adeno-associated virus (AAV) serves as a broadly used vector system for in vivo gene delivery. The process of AAV capsid assembly remains poorly understood. The viral cofactor assembly-activating protein (AAP) is required for maximum AAV production and has multiple roles in capsid assembly, namely, trafficking of the structural proteins (VP) to the nuclear site of assembly, promoting the stability of VP against multiple degradation pathways, and facilitating stable interactions between VP monomers. The N-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…An analysis of residues shared between AAV4 and AAV11 but not with AAV12 revealed a total of 23 aa. Previous studies suggested that interior residues are involved in the AAP function [ 74 , 75 ]. Only four of 23 aa differences are located in the interior of the capsid, A301S, A338T, I619V, and R688H (first aa type = AAV4/11, second aa type = AAV12).…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of residues shared between AAV4 and AAV11 but not with AAV12 revealed a total of 23 aa. Previous studies suggested that interior residues are involved in the AAP function [ 74 , 75 ]. Only four of 23 aa differences are located in the interior of the capsid, A301S, A338T, I619V, and R688H (first aa type = AAV4/11, second aa type = AAV12).…”
Section: Resultsmentioning
confidence: 99%
“…Two charged residues ( 227 KD 228 ) were also conserved among all the strains of PCV1 and PCV2. In general, strictly conserved residues in viral structure proteins, particularly when exposed on the surface of the virus, may play important roles in the life cycle of the virus, such as virus-host interactions, virion assembly, cell entry, and/or egress from host cells (45,46). Second, the 3D structure from X-ray crystallography (4) of PCV2 VLPs demonstrated that the CT (red) is located adjacent to the edge of the 5-fold axes of the capsid, which was decorated by loop BC (blue) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Infection of BEV-Rep2Cap2, which was made following the Kotin strategy of Bac-AAV2Rep-Cap [56], expressed AAP in Sf9 cells, and knockout of the AAP decreased rAAV2 yield by 10 times [55]. This suggested that the AAP plays an important role in rAAV vector production in Sf9, which is likely through facilitation of the assembly of AAV capsids [22][23][24]. We currently do not know whether HBoV1 cap also expresses an AAP-like protein that may facilitate the assembly of the HBoV1 capsid, which warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Three AAV Cap proteins, VP1, VP2 and VP3, are expressed from the mRNA transcribed by the P40 promoter [2,19]. In addition, a small NS protein, assembly-associated protein (AAP), is alternatively translated from the P40-transcribed Cap-coding mRNA [20], which plays a role in capsid assembly [21][22][23][24]. Recently, another small NS protein, membrane-associated accessory protein (MAAP), has been identified, which is also expressed from the P40-transcribed mRNA through alternative translation [25].…”
Section: Introductionmentioning
confidence: 99%